Temple with the Shekhari Shikhara - Temples of India Project Team (Jio Institute, 2024)
This is the front elevation of the temple with the shekhari shikhara in the Mahanaleshwar temple complex. The temple is in ruinous condition. Seen here are the architectural fragments of the temple which are lying in the vicinity of the temple. The mandapa (pillared hall) of the temple has fallen leaving behind only the outer stone frame.